An examination of major works for wind band and brass ensemble: “Funeral march for brass choir” by Edvard Grieg, “Dance mix” by Rob Smith, and “An original suite” by Gordon Jacob - Sobba, Lyle Andrew (Kansas State University, 2011)
The following report is research and analysis of major wind band literature for the Graduate Conducting Recital performed by the Kansas State University Wind Ensemble on March 13th, 2011 under the direction of Lyle Sobba. The repertoire for the concert was comprised of the following pieces: Funeral March for Brass Choir by Edvard Grieg, Dance Mix by Rob Smith, and An Original Suite by Gordon Jacob. This examination, through thorough research and theoretical analysis, is a compilation of the documents created to effectively rehearse the compositions. The report also contains documents pertaining to the planning and executing of the Graduate Conducting Recital.
Keywords: Music; Grieg; Smith; Jacob; Wind Band; Sobba; Music (0413); Musical Performances (0943)